CLEAN CLOTHES CAMPAIGN (CCC) EFFORTS TO IMPROVE THE HUMAN RIGHTS OF FAST FASHION INDUSTRY WORKERS IN BANGLADESH 2016-2019 - Veta Setya Lambiombir (: 2621-0924)
This study aims to analyze the efforts made by the Clean Clothes Campaign (CCC) in improving the human rights of fast fashion industry workers in Bangladesh in 2016-2019. This research is a qualitative descriptive study using the concept of human rights and transnational social movements. The researcher obtained the data from various scientific journals, books, news, and articles related to the object under study. The research findings show that the efforts made by the Clean Clothes Campaign (CCC) are campaigning for changes in the work environment to be more humane for workers in the fast fashion industry by voicing various human rights violations that befallen workers on the international stage. This effort was pursued by establishing the standard pledge of The Transparency Pledge and an invitation to use #GoTransparent on social media for the international society to help urge companies to sign The Transparency Pledge. In order to gather people's attention in one collective action for its campaign, Clean Clothes Campaign (CCC) takes three steps in framing the issue of human rights violations of fast fashion workers in Bangladesh, namely: (a) diagnostic framing (b) prognostic framing (c) motivational framing.Keywords: Bangladesh, Clean Clothes Campaign, Fast Fashion, Human Rights, Transnational Social Movement.